2022
DOI: 10.1371/journal.pone.0269745
|View full text |Cite
|
Sign up to set email alerts
|

Examining delays in diagnosis for slipped capital femoral epiphysis from a health disparities perspective

Abstract: Slipped Capital Femoral Epiphysis (SCFE) is a skeletal pathology affecting adolescents which requires timely surgery to prevent progression. Delays in diagnosis and treatment of SCFE can negatively affect patient prognosis, and few studies have examined how health disparities and barriers to care may influence these delays. In particular, only a handful of studies have included a Hispanic patient sample, despite this ethnic group’s increased risk for the disease and unique barriers to care. A retrospective cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…19 Surgeons may have been concerned about losing patients to follow-up, as a more extended time to diagnosis correlates with more severe slips. 20 However, as suggested by Guzek et al in 2022, implicit bias among surgeons may also play a role. 21 Future research should determine if race is a risk factor for contralateral SCFE and examine the role of implicit bias in this subjective surgical decision-making.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…19 Surgeons may have been concerned about losing patients to follow-up, as a more extended time to diagnosis correlates with more severe slips. 20 However, as suggested by Guzek et al in 2022, implicit bias among surgeons may also play a role. 21 Future research should determine if race is a risk factor for contralateral SCFE and examine the role of implicit bias in this subjective surgical decision-making.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have determined that racially minoritized patients were at the greatest risk of losing access to medical care due to COVID-19 19 . Surgeons may have been concerned about losing patients to follow-up, as a more extended time to diagnosis correlates with more severe slips 20 . However, as suggested by Guzek et al in 2022, implicit bias among surgeons may also play a role 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients of lower SES may fare worse, with reports of early loss to follow-up, delayed diagnosis, and greater slip severity in this demographic. 14,15 Aside from this association, the increasing incidence of SCFE is cause for concern independently. SCFE is a frequently missed diagnosis, due to its various presentations and similarity to more common and relatively benign conditions leading to delays in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort of 486 children with SCFE found that diagnostic delays were common and radiographic severity worsened with increased time to diagnosis 36 . A retrospective review of patients treated surgically for SCFE found that patients with private insurance were more likely to present with a mild slip (23%) than those who were uninsured (0%) or had Medicaid (15%), emphasizing that these diagnostic delays are associated with increased slip angles 37 .…”
Section: Slipped Capital Femoral Epiphysis (Scfe)mentioning
confidence: 99%